Investigating determinants of energy saving management of construction enterprises on the low carbon economy platform - Klymchuk, M. (Ways to Improve Construction Efficiency, 2019)
The article analyzes the prospects of implementation of the adopted "Strategy of Low Carbon Development of Ukraine till 2050", the imperatives of its implementation are proposed. On the basis of the synthesis of modern concepts of invariant and low carbon economics, a hierarchy of formation of the invariant space of the energy saving management system has been developed. The invariant imperatives of energy saving management are distinguished in terms of the levels of the economic system that influence the quality of strategic management, which contributes to increasing the level of energy efficiency and reducing the adverse climatic changes.